When genes turn traitor: de novo transcriptomics uncovers pearl millet’s rancidity machinery - Kumar, Ranjeet R.; Goswami, Suneha; Thimmegowda, Vinutha; Singhal, Nitin; Mabalirajan, Ulaganathan; Mishra, Gyan P.; Jha, Girish K.; Rai, Gyanendra K.; Praveen, Shelly; Tara Satyavathi, Chellapilla (Frontiers in Plant Science, 2025)
Pearl millet flour is highly nutritious but prone to rancidity, leading to off-odor development and reduced shelf life. To understand the molecular basis of this phenomenon, we performed de novo transcriptome sequencing on diverse pearl millet genotypes (landraces, hybrids, and composites) and identified 219,965 genes and 386,184 transcripts with functional annotation revealing key pathways linked to lipid and starch degradation. Differential gene expression (DGE) analysis identified significant upregulation of rancidity-linked genes [lipases (LIPs), lipoxygenases (LOXs), peroxidases (POXs), and polyphenol oxidases (PPOs)] in high-rancid genotypes. Data mining for characterizing rancid pathway showed the presence of 2,038 LIP, 209 Lox, 26 hydroperoxide lyase (HPL), 1,023 POX, and 17 PPO genes. Tissue-specific expression analysis of variants of Lip, Lox, Pox, and PPO during the different sub-stages of endosperm development showed an abundance of transcripts of Lip-2, LOX-3, and POX-4 during the seed hardening stage. Enzymatic assays confirmed increased LIP (up to 200.5 µmol h-1 g-1), LOX (184 nM HPOD min-1 mg-1), POX, and PPO activities in stored flour, correlating with rancidity progression. Notably, landraces exhibited lower expression of rancidity-linked genes compared to hybrids and composites, suggesting genetic variability in flour shelf life stability. Our study provides the first comprehensive transcriptomic resource for pearl millet rancidity, identifying candidate genes and enzymatic markers for future breeding programs aimed at improving flour storage quality.